The road of bones - Fine, Anne. (London : Corgi Books, 2007)
In Russia, during the reign of communism and one of the many purges that sweep the country, Yuri experiences firsthand the social injustices, labor camp, and starvation.
Young Adult.
Young Adult
Keywords: Communism -- Juvenile fiction; Families -- Soviet Union -- Juvenile fiction; Labor camps -- Juvenile fiction; Communism -- Fiction; Family life -- Soviet Union -- Fiction; Historical fiction; Labor camps -- Fiction; Communism -- Fiction; Family life -- Russia -- Fiction; Historical fiction; Labor camps -- Fiction; Siberia (Russia) -- History -- 20th century -- Juvenile fiction; Soviet Union -- History -- 1925-1953 -- Juvenile fiction; Siberia (Russia) -- History -- 20th century -- Fiction; Soviet Union -- History -- 1925-1953 -- Fiction; Russia -- History -- Fiction; Siberia (Russia) -- History -- Fiction